Markers for monitoring overtraining and recovery - Hooper, S. L.; MacKinnon, L. T.; Howard, A.; Gordon, R. D.; Bachmann, A. W. (Medicine & Science in Sports & Exercise, 1995)
Physiological measures (resting and exercise heart rates, blood pressure, oxygen consumption, blood levels of various enzymes and hormones), and subjective assessments of staleness, were monitored at five stages (early-, mid-, and late-season, in taper, and post-competition) of a six-month training program to determine if any were markers of overtraining and recovery. Ss (N = 14) were elite M and F Australian swimmers. This study showed: Once again, psychological measures have been shown to be more sensitive and related to staleness and overtraining in swimmers than physiological and biochemical measures. Monitoring psychological variables is a more fruitful and accurate direction for training stress assessment than using physiological measures. Psychological self-reports predict the occurrence of eventual performance declines. It was concluded that self-reports of well-being may provide an efficient means of monitoring both overtraining and recovery. Plasma catecholamine levels at rest, the only blood/physiological variable to hint at a response, may provide an additional measure to cross-validate the psychological indications of the states. Since physiological parameters change as a normal response to training, it is difficult to differentiate them from abnormal response associated with overtraining.